Design, culture, and transformation : design thinking at IBM (O'Reilly Media, 2017)
"In 2013, IBM, one of the world's largest technology companies, set the mission to create a sustainable culture of design. The goal: bring a human-centered focus to thousands of product and service experiences. Doug Powell offers a look at how this 350,000-employee company implemented Design Thinking and is addressing the needs of their users to deliver outcomes with speed and at scale."--Resource description page